2021
DOI: 10.3390/ijms22062980
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Glycosylation in Cancer and Other Diseases

Abstract: In the last few decades, the newly emerging field of epigenetic regulation of glycosylation acquired more importance because it is unraveling physiological and pathological mechanisms related to glycan functions. Glycosylation is a complex process in which proteins and lipids are modified by the attachment of monosaccharides. The main actors in this kind of modification are the glycoenzymes, which are translated from glycosylation-related genes (or glycogenes). The expression of glycogenes is regulated by tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 156 publications
0
9
0
Order By: Relevance
“…Aging in general leads to epigenetic mediated deregulation of genes so it is safe to assume that the glycan clock heritability estimates are not devoid of this effect ( Saldanha and Watanabe, 2015 ). Different studies reported that the process of protein glycosylation is under strong epigenetic control ( Horvat et al, 2013 ; Agrawal et al, 2014 ; Greville et al, 2016 , 2021 ; Indellicato and Trinchera, 2021 ). We hypothesize that aging related epigenetic changes such as altered DNA methylation, abnormal chromatin state, altered histone modifications and deregulation of non-coding RNAs ( Saldanha and Watanabe, 2015 ) also impact the glycan clock variation which is reflected in the inflated heritability estimates after age correction.…”
Section: Discussionmentioning
confidence: 99%
“…Aging in general leads to epigenetic mediated deregulation of genes so it is safe to assume that the glycan clock heritability estimates are not devoid of this effect ( Saldanha and Watanabe, 2015 ). Different studies reported that the process of protein glycosylation is under strong epigenetic control ( Horvat et al, 2013 ; Agrawal et al, 2014 ; Greville et al, 2016 , 2021 ; Indellicato and Trinchera, 2021 ). We hypothesize that aging related epigenetic changes such as altered DNA methylation, abnormal chromatin state, altered histone modifications and deregulation of non-coding RNAs ( Saldanha and Watanabe, 2015 ) also impact the glycan clock variation which is reflected in the inflated heritability estimates after age correction.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we observed the transcriptional upregulation of TRAIL receptors and enzymes involved in O-glycosylation, such as GALNT14, C1GALT1, and C1GALT1C1. The expression of these molecules is regulated by multiple mechanisms, including transcription factors, epigenetic modifications, and miRNAs [54,55]. Therefore, proscillaridin A may upregulate TRAIL receptor expression and O-glycosylation by affecting multiple pathways, including histone acetylation and MYC expression.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Aberrant glycosylation patterns have been linked to the development of several diseases, including genetic diseases, neurodegenerative diseases, and cancer. 25,26 Recent reports have also linked altered glycosylation expression to the development of breast cancer and cerebral metastases. 17,27−29 The serum biomarker most commonly utilized in breast cancer patients is Cancer antigen (CA) 15-3 and its effectiveness is attributed to the increased expression and altered glycosylation state of MUC-1.…”
Section: Introductionmentioning
confidence: 99%
“…N - and O -linked glycosylation are the two most significant types of protein glycosylation. Membrane glycome and secreted glycoproteins are essential in several physiological processes, including cell signaling, communication, and adhesion. Also, protein glycosylation is vital in modulating protein folding, stability, structure, and function. , Aberrant glycosylation patterns have been linked to the development of several diseases, including genetic diseases, neurodegenerative diseases, and cancer. , Recent reports have also linked altered glycosylation expression to the development of breast cancer and cerebral metastases. , The serum biomarker most commonly utilized in breast cancer patients is Cancer antigen (CA) 15-3 and its effectiveness is attributed to the increased expression and altered glycosylation state of MUC-1. MUC-1 is an extensively O -glycosylated protein and changes in its expression have been linked to the development of cancer and metastasis. Therefore, it is important to perform O -glycan profiling to understand the changes that may be involved in BCBM.…”
Section: Introductionmentioning
confidence: 99%